How Indonesian sees the colors: Natural semantic metalanguage theory - Muhammad Kiki Wardana; Mulyadi Mulyadi (JOALL (Journal of Applied Linguistics and Literature), 2022)
This research explores basic and secondary colors in Indonesia. This research attempts to explicate the meaning of colors by using the semantic theory of Natural Semantic Metalanguage Theory. This research applied qualitative method. The paradigm of qualitative research revolves around the observation from the surrounding. The data were collected from various sources such as Indonesian Dictionary, Indonesian Corpus, and the data created by the researcher as the native speaker. The researcher explicates primary or basic colors as well as the secondary. Further, these Indonesian colors were being explicated by applying the features of Natural Semantic Metalanguage (NSM). The colors in Indonesian were gathered and classified. The researcher then analyzed the colors based on the explication of NSM theory and the approach of Basic Color Term initiated by Berlin and Kay. This research discovers that the basic or primary colors in Indonesian are Black, White, Red, Yellow, Green and Blue. The application of this research is apparently vivid in the advancement of colors study in the realm of semantics.   This research also exposes the difference of explication in English and Indonesian. This occurred due to the difference of the usage of semantic atom to explain the meaning of color. To explicate the color of black, Indonesian uses charcoal. Meanwhile English uses the night sky. In Indonesian, colors that come after Green and Blue according to Berlin and Kay’s color terms are Brown, Purple, Orange, Pink, and Grey are not basics but secondary colors. Meanwhile, in English the aforementioned colors are basics.